CLUSTERING: THEORIES AND KEY PROBLEMS - Bekzodjon Aslanhojaevich, Davlyatov (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses one of the key areas of economic reform, the theoretical analysis of the clustering process, the main problems arising in the implementation of the cluster approach, and in part, the foreign experience.